Morphology-induced phonon spectra of CdSe/CdS nanoplatelets: core/shell vs. core–crown. Issue 39 (22nd September 2016) - Dzhagan, V.; Milekhin, A. G.; Valakh, M. Ya.; Pedetti, S.; Tessier, M.; Dubertret, B.; Zahn, D. R. T.
Abstract : A pronounced difference of the phonon spectra of core/shell nanoplatelets from the core-crown nanoplatelets and spherical core/shell nanocrystals is reported. Abstract : Recently developed two-dimensional colloidal semiconductor nanocrystals, or nanoplatelets (NPLs), extend the palette of solution-processable free-standing 2D nanomaterials of high performance. Growing CdSe and CdS parts subsequently in either side-by-side or stacked manner results in core–crown or core/shell structures, respectively. Both kinds of heterogeneous NPLs find efficient applications and represent interesting materials to study the electronic and lattice excitations and interaction between them under strong one-directional confinement. Here, we investigated by Raman and infrared spectroscopy the phonon spectra and electron–phonon coupling in CdSe/CdS core/shell and core–crown NPLs. A number of distinct spectral features of the two NPL morphologies are observed, which are further modified by tuning the laser excitation energy E exc between in- and off-resonant conditions. The general difference is the larger number of phonon modes in core/shell NPLs and their spectral shifts with increasing shell thickness, as well as with E exc . This behaviour is explained by strong mutual influence of the core and shell and formation of combined phonon modes. In the core–crown structure, the CdSe and CdS modes preserve more independent behaviour with only interface modes forming the phonon overtones with phonons of the core.